Analysis of student-teacher statistical reasoning ability - Ghassaniy, Nayla Nafisa; Hasanah, Aan; Wahyudin (Jurnal Pengembangan Pembelajaran Matematika (JPPM), 2023)
Researchers and teachers extensively use statistics to deepen academic knowledge or analyze students' enhancement. Therefore, many universities require their students to take a statistics class leastwise as a graduation requirement. One of the objectives of statistics class is to intensify the statistical reasoning ability of students. This study aimed to analyze the statistical reasoning level of the student-teacher. The research was conducted using a qualitative case study divided into three stages to assess students’-teacher statistical reasoning. First, we adopted the statistical reasoning task from prior research. Next, we tested 32 participants from the fourth-semester student-teacher. Finally, the statistical reasoning level was classified based on the participants' answers. The results showed that students' statistical reasoning was at the idiosyncratic, transitional, quantitative, and analytical levels, with the highest percentage at the idiosyncratic level. The conclusion was that there needs to be an effort to improve the statistical reasoning of students-teacher.